A comparative study of robot-assisted navigation versus C-arm fluoroscopy in percutaneous pedicle screw fixation for the treatment of thoracolumbar fractures - Lichuan Liang; Chen Zhao; Lei Luo; Liehua Liu; Pei Li; Yongjian Gao; Qiang Zhou (Scientific Reports)
Abstract To evaluate the clinical efficacy of ZhuZheng robot-assisted versus C-arm fluoroscopy-guided percutaneous pedicle screw fixation (PPSF) in the treatment of thoracolumbar burst fractures. A retrospective analysis was conducted on 86 patients with thoracolumbar burst fractures treated at our institution between March 2022 and August 2023. The cohort included 46 males and 40 females, aged 27 to 69 years. Patients were assigned to either the robot-assisted group (n = 41) or the conventional C-arm fluoroscopy group (n = 45) according to intraoperative navigation method. Baseline characteristics, including gender ratio and body mass index (BMI), were comparable between the two groups (P > 0.05). All patients underwent segmental fixation. Intraoperative parameters such as fluoroscopy frequency, operative time, and estimated blood loss were recorded. The accuracy of screw placement was assessed using postoperative CT at day 3 and graded according to the Gertzbein-Robbins scale. Pain was evaluated using the Visual Analogue Scale (VAS) preoperatively and at 1 day, 3 days, and 1 month postoperatively. Radiological assessments included Cobb angle and anterior vertebral height ratio at baseline, 3 days, 1 month, and 6 months postoperatively. Statistical analyses were performed using the t-test and Mann-Whitney U test. The robot-assisted group had significantly shorter operative time, reduced intraoperative blood loss, lower radiation dose, and fewer fluoroscopy exposures compared to the conventional group (all P < 0.05). No perioperative complications occurred in either group during follow-up. The screw placement accuracy (grades A + B) was significantly higher in the robot-assisted group (98.4%, 242/246) than in the conventional group (90.4%, 244/270; P < 0.05). VAS pain scores at postoperative day 1 and day 3 were significantly lower in the robot-assisted group; no significant difference was observed at 1 month. There were no significant intergroup differences in the postoperative Cobb angle or anterior vertebral height ratio at any time point (P > 0.05). Robot-assisted orthopedic surgery demonstrates significant advantages in improving screw placement accuracy, reducing intraoperative blood loss, shortening operative time, and minimizing radiation exposure and fluoroscopy frequency, thereby offering improved clinical outcomes in the management of thoracolumbar burst fractures.